Human Life Represented in Kelong Basing Tribe Kajang - Talib, Jihad; ., Nurhayati; Sahib, Harlina; Badarudin, Syafri (International Journal of Membrane Science and Technology, 2023)
An Indonesian group known as the Kajang tribe has a history of Basing Kelong after funerals. Kelong Basing is a distinctive tradition that is still practiced today. This custom hasn’t, however, been publicly recorded. Documentation needs to be completed in order for the Basing Kelong to continue to be viable and well-maintained. This study aims to illustrate how the Ammatoa people of the Kajang tribe express the path of human existence in their Basing Kelong. This study employs a qualitative descriptive methodology. The study incorporates literary ecology theories. The Ammatoa people of the Kajang tribe, who spoke Basing’s Kelong, are the source of the research’s data. Data was gathered in the field and at the library. The data were analyzed based on diction and diction strands in Basing Kelong. Diction and strings of diction are transcribed and transliterated to get messages, meanings, and values. The research succeeded in finding three representations of human life in the Basing Kelong, a resident of the Ammatoa tribe of Kajang, namely: the human biological mother is the land, which is the source of life; humans in the world are only temporary, so they must live a simple life, and humans must be patient so that in the world and the hereafter they can find happiness and serenity. These three results were obtained by using a literary ecological study approach to the Basing Kelong. Therefore, it can be concluded that the Ammatoa people of the Kajang tribe have always inherited the application of life ethics and social ethics in living life in the universe.